Innovations in Soft Computing and Information Technology Proceedings of ICEMIT 2017, Volume 3 - Chattopadhyay, Jayeeta; Singh, Rahul; Bhattacherjee, Vandana (Springer Nature Singapore : Imprint: Springer, 2019)
The book presents innovative scientific research works by academics, research scholars and students, presented at the 2017 International Conference on Energy, Materials and Information Technology at Amity University Jharkhand, India. It includes contributions on system solutions based on soft computing techniques, and covers innovative soft computing techniques and tools with advanced applications. A major focus of the book is on presenting interdisciplinary problems and how they can be solved using information technology, together with innovative connections to other disciplines. It also includes papers on cloud computing and WSN-related real-time research. .